Apology Strategies Expressed by the Characters in The Proposal Movie (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
This research is based on the fact that mistake may occur in human interaction. To minimize its effect, the interlocutor needs to apologize to his/her counterparts. This research focuses on the apology strategies, namely the ways of expressing apologies and the social functions of the apologies in â€œThe Proposalâ€ movie. Descriptive research is applied to investigate the phenomenon of apology. The data were verbal and nonverbal apology expressions taken from the English transcript of the movie. The researcher found 32 data containing apology expressed by the characters. An expression of regret comes as the dominant strategy, direct apologies are expressed more than the indirect ones and assuaging the addressee's wrath is the most dominant function of the apologies. Even though making mistakes or offence is unavoidable in human communication, by expressing an apology, the speaker will be able to minimize its effect, solve the problem, and restore the threatened relationship.